2000
DOI: 10.1002/1097-0185(20001101)260:3<299::aid-ar67>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the capillary pericytes and the expression of smooth muscle α-actin and desmin in the snake infrared sensory organs

Abstract: The infrared sensory membranes of pit organs of pit vipers have an extremely rich capillary vasculature that forms many vascular loops, each serving a small number of infrared nerve terminals. We clarified the ultrastructure of capillary pericytes in the pit membranes by scanning and transmission electron microscopy, and examined the immunoreactivity in their cytoplasm to two contractile proteins: smooth muscle α‐actin (SM α‐actin) and desmin. The capillary pericytes had two major cytoplasmic processes: thicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Goris et al (2000) speculated that the capillary pericytes were induced to relax and, thus, speed up blood flow, by a vasodilator such as nitric oxide (NO) released directly by the TNMs themselves when stimulated. Nakano et al (2000) showed that blood flow could be regulated by relaxation and contraction of capillary pericytes under the influence of such a vasodilator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goris et al (2000) speculated that the capillary pericytes were induced to relax and, thus, speed up blood flow, by a vasodilator such as nitric oxide (NO) released directly by the TNMs themselves when stimulated. Nakano et al (2000) showed that blood flow could be regulated by relaxation and contraction of capillary pericytes under the influence of such a vasodilator.…”
Section: Discussionmentioning
confidence: 99%
“…The pit membrane has a denser capillary network than any other area of skin, and the TNMs all are closely apposed to capillaries. In addition to supplying oxygen to the TNMs, the capillary network is also thought to erase infrared afterimages by cooling the TNMs (Amemiya et al, 1999; Nakano et al, 2000; Goris et al, 2000; Kishida et al, 2001).…”
mentioning
confidence: 99%
“…The pockets of the inner membrane of the basal lamina contained desmin-positive pericytessmooth muscle cells (Fig. 7C) (Diaz-Flores et al, 1991;Nakano et al, 2000). The pericytes are elongated cells forming a fibrous network surrounding larger vessels (Fig.…”
Section: The Basal Lamina Separates Astrocytes Endothelial Cells Anmentioning
confidence: 97%
“…For more than 100 years since they were described, 15,16 pericytes were considered to be contractile cells regulating vascular tone and blood flow because, anatomically, the processes of pericytes envelope EC and pericytes express contractile microfilaments (actin, myosin) and intermediate filaments (desmin, vimentin) 17–19 . Definitive functional studies have proved that pericytes control capillary diameter in whole retina and cerebellar slices 20 .…”
Section: Pericyte Functionmentioning
confidence: 99%